2021
DOI: 10.1002/mdc3.13220
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Double Vision in Parkinson Disease

Abstract: BackgroundBackground: Some patients with Parkinson Disease (PD) report double vision, but its prevalence and determinants are unknown. Objectives Objectives: To determine the prevalence and risk factors for diplopia in PD. Methods Methods: Using data from 26,790 PD patients and 9257 controls in the Fox Insight Study, we compared the prevalence of diplopia using the Non-Movement Symptom Questionnaire. Associations with age, race, gender, disease duration, and scores on MDS-UPDRS part II, and Penn Parkinson's Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Schindlbeck et al [ 3 ] detected binocular diplopia in 37 out of 125 PD patients (29.6%) who were screened for diplopia, visual hallucinations, problems with spatial perception, contrast sensitivity, presence of blurred vision, and history of ophthalmological comorbidities via interview. In a more recent longitudinal study, Hamedani et al [ 8 ] reported a point prevalence diplopia of 18.1% in 26,790 PD patients and 6.3% in a control group, being present at least once in up to 28.2% of all the patients during the study (period prevalence). In our cohort, diplopia for each transversal analysis ranged from 13.6% to 17.1% in the patients and was very low in the controls.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Schindlbeck et al [ 3 ] detected binocular diplopia in 37 out of 125 PD patients (29.6%) who were screened for diplopia, visual hallucinations, problems with spatial perception, contrast sensitivity, presence of blurred vision, and history of ophthalmological comorbidities via interview. In a more recent longitudinal study, Hamedani et al [ 8 ] reported a point prevalence diplopia of 18.1% in 26,790 PD patients and 6.3% in a control group, being present at least once in up to 28.2% of all the patients during the study (period prevalence). In our cohort, diplopia for each transversal analysis ranged from 13.6% to 17.1% in the patients and was very low in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the NMSS is useful for detecting not only the presence of a symptom, such as the NMS-Quest [ 17 ], but the frequency and severity as well, being correct to separate the patients as those without the symptom (score = 0) versus those with the symptom (score ≄ 1). In the largest study to date to detect diplopia in PD, the NMSQuest was used, being present in 28.2% of all the PD patients compared to 9.1% of controls [ 8 ]. Using the NMSS with our methodology (only one visit), Martinez-Martin et al, identified 72 out of 411 (17.5%) patients as PD patients with double vision [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations